TINGKAT KEPERCAYAAN DONATUR TERHADAP PENDISTRIBUSIAN DANA ZIS DENGAN PRINSIP KEADILAN DAN TRANSPARANSI DI LAZISNU DORO KABUPATEN PEKALONGAN - Rihadatul Aisy, Adibah Husnaa (Jurnal Manajemen Dakwah, 2024)
The Amil Zakat, Infaq and Sedekah institutions have the task of managing ZIS funds, one of which is distribution activities. In distributing zakat, infaq and alms funds, it should be managed with professional, trustworthy, fair and transparent management. This research aims to determine the level of donor trust in the distribution of ZIS funds with the principles of justice and transparency owned by the Amil Zakat Institution. This research uses qualitative methods by utilizing data in the field. The results of this research show that the Amil Zakat, Infaq and Alms Institution in Doro District has implemented the principles of justice and transparency in distributing its zakat, infaq and alms funds. Distribution is carried out using several predetermined procedures, such as registering, surveying and selecting mustahik who meet the requirements. The level of donor trust in Lazisnu Doro is influenced by several factors including openness, trustworthiness, competence and loyalty possessed by Lazisnu Doro. This research results that Lazisnu Doro's justice and transparency are part of a form of social responsibility, so this is an absolute thing to strive for and become a target for Lazisnu Doro. Transparency of financial reports and activity reports has also been implemented well. Financial reports will be provided periodically every month or every semester to interested parties, while activity reports will be provided via Lazisnu Doro social media.Keywords : Distribution, Fairness, Transparancy, Trust